Stress and Coping Mechanisms in Thesis Preparation: A Study of Undergraduate Midwifery Students at Universitas Mega Buana Palopo, 2025 - Wafiah, Nur; Fadli; Supri, Aisyah; Papayungan, Sutrisno (AACENDIKIA: Journal of Nursing, 2025)
Stress is a condition in which physical, environmental, and social factors become dysregulated. The body responds to stress originating from psychosocial factors—such as emotional pressure or life challenges—through physiological, psychological, or behavioral reactions that can become excessive and unrecognized. This study aimed to examine the relationship between stress levels and coping mechanisms during thesis preparation among undergraduate midwifery students at Universitas Mega Buana Palopo in 2025. A descriptive analytic design with a cross-sectional approach was used. The study population consisted of undergraduate midwifery students currently working on their theses. Total sampling was applied, involving 40 respondents. Data were collected using stress level and coping mechanism questionnaires, and analyzed using SPSS version 26 with the Chi-Square test. Results showed that among 40 respondents, the majority experienced moderate stress (40%). Among them, 3 students (7.5%) used adaptive coping mechanisms, while 13 students (32.5%) applied maladaptive coping mechanisms. Statistical analysis using the Chi-Square test revealed a significant relationship (p = 0.001 < 0.05) between stress levels and coping mechanisms. It can be concluded that there is a significant relationship between stress levels and coping mechanisms during thesis preparation among undergraduate midwifery students at Universitas Mega Buana Palopo in 2025.